Digital Business Training as an Effort to Expand Job Opportunities Graduates in Lampung Province - Efendi, Nur (Jurnal Puruhita, 2024)
Expanding employment opportunities is not only the responsibility of the government but also of university personnel. The job expansion program is oriented towards increasing workforce absorption and efforts to create jobs. The purpose of this Community Service activity is to expand employment opportunities by providing digital business knowledge and skills to university graduates in Lampung Province. The method used is to provide digital business training to target groups. Training activities are provided in the form of lectures and mentoring for 2 months. The target group in this activity is university graduates who are registered as job seekers at the Lampung Provincial Manpower Office. The series of digital business training activities began with training activities on Monday, July 10, 2023, at the UPT PKK Unila Training Room and ended on September 10, 2023. The speakers came from academics and practitioners in digital business and were attended by 30 participants from several universities in Lampung Province. The results of the evaluation of this PkM activity showed that although there was an increase in participant knowledge as a result of the training activities, this activity has not been able to encourage college graduates to pursue careers as entrepreneurs. There are 3.3% of the 30 participants who run digital businesses with an increase in sales turnover of 12% over 2 months.